An inclusive experience in special education (Journal of Parents and Teachers, 2013)
The Bobath Foundation is a non-profit organization dedicated, mainly, to the assistance, treatment and education of persons with Cerebral Palsy. The Foundation interacts with these persons from the first stages of their lives until the end of their vocational studies. Our goal is to help them achieve full social and occupational integration. We understand our Special Education School within the framework of an inclusive education.To that end, we design individualized programs based on a thorough evaluation of each child's needs and potential. The implementation of these programs fosters the acquisition of functional skills as they enter adulthood.  In order to develop this project, we work with a broad interdisciplinary team of professionals who are involved in ongoing training. We understand families to play an essential role in the assistance, education and treatment of their children.
Keywords: Bobath concept; inclusive school; individualized education; family involvement throughout the educational project; continuity in adulthood; experiences; education.